ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENERBITAN GOING CONCERN WARNINGS (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017) - Nisrina Nugeraheny; Imam Ghozali (Diponegoro Journal of Accounting, 2019)
The aim of this study is to discuss the relationship of auditor formal competence, audit fee, and audit firm size in issuing going concern warnings. This study uses leverage and client size as a control variables.This study uses companies in the manufacturing sector that are listed on the Indonesia Stock Exchange in 2017 as population. Sampling determined with purposive sampling method. Total sample of this research is 66 companies.This study uses a logistic regression analysis test tool. The results of this study indicates that auditor formal competence and audit fee has a positively related to auditor likehood of issuing going concern warnings, while audit firm size has a negatively related to auditor likehood of issuing going concern warnings.